Analisis Hukum Kasus Pemecatan 249 Tenaga Kesehatan di NTT Sebagai Akibat dari Berserikat - Zulfikar, Faiz Raudhin; Bintang, Airiique; Fadhilah, Muhamad Arif (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The dismissal of 249 health workers in East Nusa Tenggara (NTT) for demonstrating has caused controversy. The non-ASN health workers requested a salary increase and appointment as government employees with labour agreements. Their demonstration in front of the Manggarai DPRD on 6 March 2024 triggered the Regent's decision not to extend the 2024 Work Order Letter (SPK), which meant the dismissal of 249 non-ASN health workers. This case shows that Indonesia's labour system is still vulnerable to pressure and oppression as well as arbitrary actions by one party. This legal analysis discusses the rights and obligations of workers and the government as well as the implications of this case for labour in Indonesia. In this research, the author uses normative legal methods to analyse the Law of the Republic of Indonesia Number 36 of 2014 on Health Workers and related Government Regulations and other literature. The results of the analysis show that the dismissal of health workers is not in accordance with legal provisions and has the potential to cause disputes. Therefore, there needs to be changes and improvements in the Indonesian labour system to protect workers' rights.